2016
DOI: 10.1111/jgh.13028
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous thermal ablation for primary hepatocellular carcinoma: A systematic review and meta‐analysis

Abstract: Overall, both RFA and MWA are equally effective and safe, but MWA may be more effective compared to RFA in preventing LTP when treating larger tumors. Well-designed, larger, multicentre RCTs are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 39 publications
3
62
2
1
Order By: Relevance
“…This result is in close agreement with a previous study in which complete tumor necrosis has been correlated with reduced risk of posttransplantation tumor recurrence . Hence, complete tumor necrosis is the goal of any treatment modality, including emerging therapies such as microwave ablation and stereotactic body radiotherapy . In order to achieve the so‐called “holy grail” of complete necrosis, the treatment paradigm for RFA of liver tumors requires a sufficient ablation margin beyond the visible tumor margin to ensure ablation of infiltrative and/or microscopic disease that may not be visible by current imaging methods.…”
Section: Discussionsupporting
confidence: 89%
“…This result is in close agreement with a previous study in which complete tumor necrosis has been correlated with reduced risk of posttransplantation tumor recurrence . Hence, complete tumor necrosis is the goal of any treatment modality, including emerging therapies such as microwave ablation and stereotactic body radiotherapy . In order to achieve the so‐called “holy grail” of complete necrosis, the treatment paradigm for RFA of liver tumors requires a sufficient ablation margin beyond the visible tumor margin to ensure ablation of infiltrative and/or microscopic disease that may not be visible by current imaging methods.…”
Section: Discussionsupporting
confidence: 89%
“…Current literature concerning complete ablation and LTP rates of MWA versus RFA are controversial [33, 34]. In our study, a lower incidence of LTP was observed in the MWA group compared with the RFA group.…”
Section: Discussionsupporting
confidence: 47%
“…The two meta-analysis published so far in this field reported no difference 3-year OS with MWA outperforming RFA in terms of LR for treatment of larger tumours[99,100]. However, further RCTs are needed to verify whether MWA efficacy in determining broader ablation areas will translate into a real survival benefit.…”
Section: Other Thermal Ablation Techniquesmentioning
confidence: 99%